Maternal suicide during pregnancy and the first postpartum year in Austria: Findings from 2004 to 2017. (November 2019) - Knasmüller, Philipp; Kotal, Aglaia; König, Daniel; Vyssoki, Benjamin; Kapusta, Nestor; Blüml, Victor
Highlights: Between 2004 and 2017 we found 10 suicides of pregnant/postpartal women in Austria. The comparably low number of found suicides is arguably attributable to methodological issues in identifying perinatal suicides. A more comprehensive inquiry into perinatal deaths and further improvements in perinatal mental health care are called for. Abstract: Suicide is one of the leading causes of maternal death during pregnancy and the first postpartum year. This retrospective investigation aimed at characterizing suicides in Austria during pregnancy and the first postpartum year between 2004 and 2017. We identified 10 suicides of pregnant/ postpartal women in that period, all of whom used violent methods, resulting in a maternal suicide rate of 0.89 per 100, 000 birth events. The comparably low number of found suicides is arguably attributable to methodological issues in identifying perinatal suicides. Hence, a more comprehensive inquiry into perinatal deaths and further improvements in perinatal mental health care are called for.